Application of Foot Massage Therapy to Reduce Pain in Post-Caesarean Section Patients - Kasim, Erna; Ibrahim, Windi; Limbong, Magdalena; Hafida, Ekayanti (LPPM STIKes Muhammadiyah Ciamis, 2025)
Caesarean section (C-section) is a surgical procedure involving an incision through the abdominal and uterine walls to deliver the fetus. This procedure disrupts tissues, blood vessels, and nerves, often resulting in postoperative pain. Pain management strategies include both pharmacological and non-pharmacological interventions. Foot massage is one non-pharmacological approach involving skin stimulation techniques. To examine the application of foot massage therapy in reducing pain among post-C-section patients. This research used a descriptive case study design and was conducted at RSUD Labuang Baji Hospital, Makassar, over six days. Two participants who met the inclusion criteria (first-day post-C-section, aged 20–30, moderate pain level) were selected. Exclusion criteria included uncooperative behavior, loss of consciousness, or severe bleeding. Data collection involved interviews, observations, and documentation. Instruments included a standard operating procedure (SOP) for foot massage and the Numeric Rating Scale (NRS) for pain assessment. Results were presented in narrative and tabular formats. Both participants showed a reduction in pain levels after receiving foot massage therapy. Participant N reported pain decreasing from 6 to 2 over three days, while participant S experienced a decrease from 5 to 3. The decrease was more significant in participant N, who received consistent family support and practiced the therapy more regularly. Conclusion: Foot massage therapy may help reduce pain in post-C-section patients. It is recommended as a supportive, non-pharmacological option in postoperative care.